2015
DOI: 10.1007/s12032-014-0367-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic values of alpha-fetoprotein, dickkopf-1, and osteopontin for hepatocellular carcinoma

Abstract: The timely diagnosis and effective treatment are essential for improving the survival and prognosis of hepatocellular carcinoma (HCC) patients. Alpha-fetoprotein (AFP) is the most widely used biomarker for diagnosis of HCC, but the low sensitivity and specificity limits its clinical application. In this study, we evaluated the diagnostic capability of the combination of AFP with two novel potential biomarkers, dickkopf-1 (DKK1) and osteopontin (OPN), for HCC in 390 participants including 89 patients with HCC, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 39 publications
8
56
0
Order By: Relevance
“…In this study, serum DKK-1 level was significantly higher in HCC patients than those of cirrhotic and healthy groups, while there was no significant difference in DKK1 levels between cirrhotic and control groups. This was in accordance with what was stated by many authors (16)(17)(18)(19)(20) ; as they found that DKK1 levels were significantly higher in HCC and could distinguish HCC patients from cirrhotic patients and from healthy controls.…”
Section: Discussion:-supporting
confidence: 93%
“…In this study, serum DKK-1 level was significantly higher in HCC patients than those of cirrhotic and healthy groups, while there was no significant difference in DKK1 levels between cirrhotic and control groups. This was in accordance with what was stated by many authors (16)(17)(18)(19)(20) ; as they found that DKK1 levels were significantly higher in HCC and could distinguish HCC patients from cirrhotic patients and from healthy controls.…”
Section: Discussion:-supporting
confidence: 93%
“…Furthermore, we showed that the performance of OPN remained intact a year prior to HCC diagnosis in this high risk group (8, 9). The performance of OPN for the early detection of HCC was further validated in independent studies (1012). OPN is an extracellular matrix protein that has been implicated in several carcinogenic and angiogenic processes, such as cell invasion, inflammation, tumor progression, and metastasis (13, 14).…”
Section: Introductionmentioning
confidence: 96%
“…Also, the sensitivity and specificity of our model are higher than that of other HCC markers like for AFP, they were 61 and 71 %; for DCP, 39 and 90 %; for AFP-L3, 37 and 92 %; for dickkopf-1 (DKK1), 69.1 and 90.6; and for osteopontin (OPN), 74 and 66 %, respectively. Also, our outcomes are superior to that of AFP and AFP-L3 combination, 77 % sensitivity; AFP and DCP combination, 59 % sensitivity; and AFP, DKK1 and OPN combination, 88.76 % [6,[33][34][35][36]. Moreover, the GPC-HCC model has higher sensitivity than do other GPC3 and AFP combinations.…”
Section: Discussionmentioning
confidence: 79%